Penguatan Kemampuan Berbahasa Indonesia Melalui Pelatihan Penulisan dan Berbicara bagi Masyarakat di Gampong Meunasah Drang, Aceh Utara - Ahyar, Juni; Safriandi; Harliyana, Iba; Pahlevi Ginting, Reza; Zulfadli (Jurnal Solusi Masyarakat (JSM), 2025)
This community service program aims to enhance the proficiency of the Meunasah Drang community, Krueng Mane, North Aceh, in using the Indonesian language, particularly in speaking and writing according to proper linguistic rules. The initiative was motivated by the need to foster effective communication and improve language literacy among local residents, which is essential for social interaction and everyday activities. The program was implemented through interactive training sessions, combining theoretical explanations with hands-on practice, group discussions, and guided writing exercises. Participants were encouraged to actively engage in dialogues and create written works that reflect correct language structures. The outcomes of the activities demonstrated a significant improvement in participants' understanding and ability to use the Indonesian language accurately and effectively. Furthermore, the training fostered greater awareness of language as a tool for cultural expression and social cohesion. The success of this program highlights the importance of continuous language education and its impact on improving community literacy.